What are the valuable lessons from global research on environmental literacy in the last two decades? A systematic literature review - Husamah, H.; Rahardjanto, Abdulkadir; Hadi, Samsun; Lestari, Nurdiyah (Biosfer: Jurnal Pendidikan Biologi, 2024)
Publications on environmental literacy (EL) in reputable international journals have continued to increase and develop in the last two decades, making it interesting to study. This systematic literature review (SLR) aims to investigatively review various studies published in journals indexed in the Scopus database related to EL. The review focuses on publication trends and valuable lessons to be learned from global research over the past two decades. We used the phrase “environmental literature” in the Scopus disbursement menu and found 296 articles. The inclusion and exclusion model used is PRISMA, so only 37 articles met the criteria to be analyzed. Data shows that EL publications have fluctuated, starting to increase in number from 2017 to 2023 although it had decreased in 2021. EL publications are mostly researched using quantitative methods, and some with qualitative, mix-method, and R&D. The dominant name in EL studies is F. X. Bogner. The two main keywords related to the EL keyword are environmental education and knowledge. Most of the articles published are collaborative, both internationally and between universities within one country. We discussed the valuable lessons in question, namely the sample size, gender, institution level, and main goal of each article. These findings can serve as a consideration or baseline for researchers to study EL according to their respective interests, needs and missions.